Tren layanan sirkulasi perpustakaan menggunakan teknologi RFID: Kajian literatur di UIN Sunan Ampel Kampus Gunung ?Anyar Surabaya - Samidah Nurmayuni; Abdun Nashir (IJAL (Indonesian Journal of Academic Librarianship), 2022)
The purpose of this study is to understand the implementation of RFID in the circulation service at UIN Sunan Ampel Library, Gunung Anyar Campus. One way to improve library services using information and communication technology is by utilizing Radio Frequency Identification (RFID) technology. With RFID, users can engage in self-service, enabling them to perform borrowing and returning processes independently. The advantage of this self-service is to enhance time efficiency by speeding up the circulation process. The research method employed in this study is literature review, involving the collection and analysis of various literature sources regarding trends in library circulation services. The findings indicate that libraries can adopt smart technologies such as Augmented Reality (AR), Virtual Reality (VR), Internet of Things (IoT), and gaming. The use of these technologies aims to alleviate librarians' workload, facilitate user access to library services, and provide new and engaging experiences for users, thereby increasing their interest in visiting the library. The conclusion of this study emphasizes the importance of libraries, particularly in the circulation field, to continuously adapt to user needs. Therefore, libraries should follow current emerging trends to remain relevant.